122k views
25 votes
The question is below:

The question is below:-example-1

1 Answer

5 votes

Hello There!!

Given


3(x - 2) + 7x = (1)/(2) (6x - 2)

Solving It


3(x - 2) + 7x = (1)/(2) (6x - 2) \\ \\ \implies3x - 6 + 7x = ([(1)/(2) * 6 \: x] - [(1)/(2) * 2]) \\ \\ \implies10x - 6 = ([(1)/( \cancel2) * \cancel 6 \: x] - [(1)/( \cancel2) * \cancel2]) \\ \\ \implies 10x - 6 = 3x - 1 \\ \\ \fbox{Bringing (3x )to left side whereas( - 6 )in right side} \\ \\ \implies10x - 3x = - 1 + 6 \\ \\ \implies7x = 5 \\ \\ \therefore x = (5)/(7)

The Solution is =
(5)/(7)


\text\red{One Solution set is possible.}

Hope This Helps

User NSExceptional
by
4.6k points